On the Extension of the Present Time. Accounts for a Temporally Oriented Sociology with Georg Simmel: Insights Regarding a Research Experience - Botia Merchán, H. Augusto; Acevedo, Einer (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
This working paper arises from the conviction that it is possible to propose a temporally oriented sociology with Georg Simmel. From his idea of the extension of the present, which belongs to his philosophy of history as to his sociology and philosophy of life, this paper looks forward to contributing to discussions related to historical experience, as well as collective and cultural memory, and social imagination. Framed within an ongoing research experience on future imaginaries of former guerrilla fighters in process of re-incorporation to the civilian life in the city of Medellin (Colombia), and resorting to other authors with problematizations on the present as a particular mediator between past and future, we state that an extended present in which a fundamentally traumatic past is constantly stalking and conditioned to the expectancies concerning the fiction of the new beginning characteristic of the post-conflictual imaginary is a particular feature of the Colombian temporal regime.